2021
DOI: 10.3389/fphys.2021.745194
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Antioxidant Effects Between Hydrogen Gas Inhalation and Vitamin C Supplementation in Response to a 60-Min Treadmill Exercise in Rat Gastrocnemius Muscle

Abstract: The reactive oxygen species (ROS) produced during exercise act as a double-edged sword because they may cause oxidative damage but also play a role in the signaling pathways. A supplementation of exogenous antioxidants can reduce the total amount of ROS during exercise while it may also affect the ROS’ role in the signaling pathways of mitochondrial biogenesis. It has been suggested that hydrogen gas, as an antioxidant, can selectively scavenge hydroxyl radicals but does not affect superoxide anion’s signal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The promotion of mitochondrial biogenesis by H 2 has been previously reported, as demonstrated by increased expression of mtDNA (mtCoxII, mtCoxIV, and mtNd1) and mitochondrial biogenesis-related genes (Pgc-1α, Tfam, Nrf-1/2, and Pparγ) (Chaoqun et al, 2021;Xie et al, 2021;Luo et al, 2022;Zhang et al, 2023). The H 2 -induced mitochondrial biogenesis may be mediated by PPARγ/AMPK/SIRT1-PGC-1α-NRF1/2-TFAM pathway (Chaoqun et al, 2021;Xie et al, 2021;Luo et al, 2022). In addition to the regulation at transcriptional level, mitochondrial biogenesis can also be governed by post-translational processes, such as mitochondrial protein import regulation (Devaux et al, 2010).…”
Section: Promotion Of Mitochondrial Biogenesismentioning
confidence: 53%
See 1 more Smart Citation
“…The promotion of mitochondrial biogenesis by H 2 has been previously reported, as demonstrated by increased expression of mtDNA (mtCoxII, mtCoxIV, and mtNd1) and mitochondrial biogenesis-related genes (Pgc-1α, Tfam, Nrf-1/2, and Pparγ) (Chaoqun et al, 2021;Xie et al, 2021;Luo et al, 2022;Zhang et al, 2023). The H 2 -induced mitochondrial biogenesis may be mediated by PPARγ/AMPK/SIRT1-PGC-1α-NRF1/2-TFAM pathway (Chaoqun et al, 2021;Xie et al, 2021;Luo et al, 2022). In addition to the regulation at transcriptional level, mitochondrial biogenesis can also be governed by post-translational processes, such as mitochondrial protein import regulation (Devaux et al, 2010).…”
Section: Promotion Of Mitochondrial Biogenesismentioning
confidence: 53%
“…The activation of this PGC-1α/NRF-1/2/TFAM pathway leads to the synthesis of mitochondrial DNA and proteins and generation of new mitochondria (Popov, 2020). The promotion of mitochondrial biogenesis by H 2 has been previously reported, as demonstrated by increased expression of mtDNA (mtCoxII, mtCoxIV, and mtNd1) and mitochondrial biogenesis-related genes (Pgc-1α, Tfam, Nrf-1/2, and Pparγ) (Chaoqun et al, 2021;Xie et al, 2021;Luo et al, 2022;Zhang et al, 2023). The H 2 -induced mitochondrial biogenesis may be mediated by PPARγ/AMPK/SIRT1-PGC-1α-NRF1/2-TFAM pathway (Chaoqun et al, 2021;Xie et al, 2021;Luo et al, 2022).…”
Section: Promotion Of Mitochondrial Biogenesismentioning
confidence: 86%
“…Animal studies demonstrate that H 2 treatment attenuated the exercise-induced increases in skeletal muscle TNF-α, NF-κB, IL-6, and caspase-3 levels while increasing superoxide dismutase levels [20]. Moreover, another study found that compared to but unlike vitamin C, H 2 treatment did not reduce the exercise-induced elevated levels of peroxisome proliferator-activated receptor-gamma (PPARγ) coactivator-1alpha (PGC-1α), nuclear transcription factors 1-2 (NRF-1,2), and mitochondrial transcription factor A (TFAM) [27]. These studies indicate that H 2 can reduce excessive levels of inflammation and oxidative stress, but does not interfere with favorable exercise-induced adaptations in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant, such as N-acetylcysteine (NAC), Vitamin C, Vitamin E, can scavenge ROS, prevent oxidative stress and damage. 69,81,82 These are all important approaches to inhibit AGEs.…”
Section: Chemicals Against Advanced Glycation End Productsmentioning
confidence: 99%
“…Antioxidants can help reduce oxidative stress, lowering AGEs generation. Antioxidants assist in scavenging free radicals, decreasing the oxidation of proteins, lipids and nucleic acids, thereby slowing down AGEs formation 11,35,69 …”
Section: Eliminations Of Advanced Glycation End Productsmentioning
confidence: 99%